The nymph of Anacroneuria payagua Froehlich (Plecoptera: Perlidae) from Brazil - Righi-Cavallaro, Karina O.; Froehlich, Claudio G. (Zootaxa, 2013)
The unknown nymph of Anacroneuria payagua Froehlich is described based on the association with reared adult females from streams located in Mato Grosso do Sul State, Brazil. Anacroneuria guaikuru Froehlich also occurred in these streams.